2011
DOI: 10.1177/153303461101000604
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Response to Primary Medical Therapy for Breast Cancer Using Three-Dimensional Time-Resolved Optical Mammography

Abstract: Primary medical therapy is used to reduce tumour size prior to surgery in women with locally advanced breast cancer. Optical tomography is a functional imaging technique using nearinfrared light to produce three-dimensional breast images of tissue oxygen saturation and haemoglobin concentration. Its advantages include the ability to display quantitative physiological information, and to allow repeated scans without the hazards associated with exposure to ionising radiation. There is a need for a non-invasive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…179 Several studies discussed the time-dependent change of the tumor functional properties over different treatment cycles, in part until the end of NAC. 141,169,172,173,[180][181][182] Pakalniskis et al 141 reported that tumor HbT decreases significantly during NAC for pathologic complete responders and not for partial responders. A similar trend is visible in the long-term tumor data of Falou et al 172,173 Schaafsma et al 182 focused on the investigation of patients with HER2-negative breast cancer, which is associated with decreased angiogenesis resulting in less pronounced differences in HbT between tumor and healthy tissue.…”
Section: Monitoring Patient Response To Neoadjuvant Chemotherapymentioning
confidence: 99%
“…179 Several studies discussed the time-dependent change of the tumor functional properties over different treatment cycles, in part until the end of NAC. 141,169,172,173,[180][181][182] Pakalniskis et al 141 reported that tumor HbT decreases significantly during NAC for pathologic complete responders and not for partial responders. A similar trend is visible in the long-term tumor data of Falou et al 172,173 Schaafsma et al 182 focused on the investigation of patients with HER2-negative breast cancer, which is associated with decreased angiogenesis resulting in less pronounced differences in HbT between tumor and healthy tissue.…”
Section: Monitoring Patient Response To Neoadjuvant Chemotherapymentioning
confidence: 99%
“…These changes have also been noted by other researchers. [97][98][99][100][101][102] The change in DOSI values were compared between pCR (N ¼ 11) and nonpCR (N ¼ 25) groups to assess whether DOSI can predict pathological response early during NAC. At the treatment midpoint, the ratio of the TOI between tumor and normal tissue dropped 47 AE 8% for pCR and 20 AE 5% for nonpCR subjects.…”
Section: Fdpm Application: Breast Oncologymentioning
confidence: 99%
“…These changes in the healthy Q6 breast tissue are not surprising as certain chemotherapy agents can cause anaemia in some patients, which will affect the whole body. Other studies have shown that the background tissue physiological properties remain relatively stable in some patients, while other patients show changes in the background breast physiological properties over the course of treatment (Enfield et al 2011).…”
Section: Discussionmentioning
confidence: 97%